2020
DOI: 10.35808/ijeba/522
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Passion and Self-Efficacy as Factors Explaining Innovative Behavior: A Mediation Model

Abstract: Purpose: Dynamic and successful entrepreneurs and an enabling business environment are necessary if a company has to grow sustainably. However, research on the most important factors for entrepreneurs to be successful is still scarce. This paper analyzes the mediating effect of entrepreneurial passion-a key trait in successful entrepreneurs-on the relationship between entrepreneurial self-efficacy and innovative behavior. Design/Methodology/Approach: Partial least squares structural equation modeling (PLS-SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 81 publications
2
13
0
Order By: Relevance
“…Lastly, self-efficacy influences people’s effective responses to approaching tasks, which in turn influences the degree of successful completion of the task. In simpler words, when the individuals believe that they can generate the desired result through their actions, they are more likely to act and achieve them [ 37 ]. This is because the level of self-efficacy influences motivation, effort, perseverance in the face of difficulty, emotional stability, and stress levels [ 38 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Lastly, self-efficacy influences people’s effective responses to approaching tasks, which in turn influences the degree of successful completion of the task. In simpler words, when the individuals believe that they can generate the desired result through their actions, they are more likely to act and achieve them [ 37 ]. This is because the level of self-efficacy influences motivation, effort, perseverance in the face of difficulty, emotional stability, and stress levels [ 38 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The role of entrepreneurship in difficult times is crucial because leaders of many companies are being forced to innovate and even change their business models. The study conducted by Noreña-Chavez and Guevara [78] concluded that entrepreneurial self-efficacy can be an essential factor affecting innovative behavior during a crisis such as a pandemic. Likewise, during an economic crisis, strong entrepreneurial self-efficacy allows SME owners or managers to fight against the crisis by implementing innovations.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…The strategic outlook requires the company to have a clear strategic plan to support the innovation process and to have specific and documented projects and work plans that are applicable and evaluated to achieve the company's strategic vision, and a methodology to support and finance development and commitment projects by senior management to support those efforts. The strategic perspective encouraged employees to expand beyond their expectations of the achievement and the critical change required and developed to achieve it (Al-Obaidiyen, 2009;Norena-Chavez and Guevara, 2020).…”
Section: H011mentioning
confidence: 99%